Telomere dynamics in the lower plant Physcomitrella patens - Fojtová, Miloslava; Sýkorová, Eva; Najdekrová, Lucie; Polanská, Pavla; Zachová, Dagmar; Vagnerová, Radka; Angelis, Karel J; Fajkus, Jiří (Plant molecular biology, 2015)
A comparative approach in biology is needed to assess the universality of rules governing this discipline. In plant telomere research, most of the key principles were established based on studies in only single model plant, Arabidopsis thaliana. These principles include the absence of telomere shortening during plant development and the corresponding activity of telomerase in dividing (meristem) plant cells. Here we examine these principles in Physcomitrella patens as a representative of lower plants. To follow telomerase expression, we first characterize the gene coding for the telomerase reverse transcriptase subunit PpTERT in P. patens, for which only incomplete prediction has been available so far. In protonema cultures of P. patens, growing by filament apical cell division, the proportion of apical (dividing) cells was quantified and telomere length, telomerase expression and activity were determined. Our results show telomere stability and demonstrate proportionality of telomerase activity and expression with the number of apical cells. In addition, we analyze telomere maintenance in mre11, rad50, nbs1, ku70 and lig4 mutants of P. patens and compare the impact of these mutations in double-strand-break (DSB) repair pathways with earlier observations in corresponding A. thaliana mutants. Telomere phenotypes are absent and DSB repair kinetics is not affected in P. patens mutants for DSB factors involved in non-homologous end joining (NHEJ). This is compliant with the overall dominance of homologous recombination over NHEJ pathways in the moss, contrary to the inverse situation in flowering plants.
Keywords: sekvence nukleotidů; fenotyp; Phenotype; mutace; telomerasa; Arabidopsis; fylogeneze; Sequence Analysis, DNA; Phylogeny; Homologous Recombination; sekvenční analýza DNA; molekulární sekvence - údaje; Amino Acid Sequence; mechy; Sequence Alignment; dvouřetězcové zlomy DNA; DNA Breaks, Double-Stranded; sekvenční seřazení; Bryopsida; chromozomy rostlin; Plant Proteins; Telomere Homeostasis; homologní rekombinace; Chromosomes, Plant; DNA rostlinná; DNA Repair; oprava DNA; DNA, Plant; Telomerase; telomery; sekvence aminokyselin; Molecular Sequence Data; Base Sequence; homeostáza telomer; Mutation; Telomere; rostlinné proteiny